Chemoembolization related to good survival for selected patients with hepatocellular carcinoma invading segmental portal vein. (12th March 2018) - Kim, Jin Hyoung; Shim, Ju Hyun; Yoon, Hyun‐Ki; Ko, Heung‐Kyu; Kim, Jong Woo; Gwon, Dong Il
Abstract: Background & Aims: We evaluated survival outcomes and prognostic factors associated with survival after TACE in a large cohort of 331 patients with HCC with segmental PVTT. Methods: From 1997 to 2015, a total of 331 patients were included in this study from among 507 patients who underwent TACE as a first‐line treatment for HCC with segmental PVTT. Results: After TACE, the median survival of the whole cohort was 10.7 months, and the 1‐year, 3‐year and 5‐year survival rates were 44.9%, 16% and 12% respectively. Objective tumour response after TACE was achieved in 53.8% of patients. Multivariable Cox regression analyses confirmed that up‐to‐11 criteria, extrahepatic metastasis, Child–Pugh class, and tumour response to TACE were independent prognostic factors for patient survival. The expected median survival times among patients with 0, 1 and 2‐4 risk factors were 29.1, 15.1 and 5.3 months respectively. The 30‐day mortality and major complications rates after TACE were 0.9% and 5.4% respectively. Conclusions: TACE was well‐tolerated and effective in selected patients with HCC with segmental PVTT. We found that four risk factors were associated with decreased length of patient survival after TACE: a major tumour burden (up‐to‐11 criteria out), extrahepatic spread, Child–Pugh class B liver function and nonregression to TACE. TACE may not be recommended for HCC patients with segmental PVTT with 2‐4 risk factors because of poor survival outcome.